2015
DOI: 10.1177/1069072714565856
|View full text |Cite
|
Sign up to set email alerts
|

Career Adapt-Abilities Scale–Short Form (CAAS-SF)

Abstract: The Career Adapt-Abilities Scale (CAAS) has become one of the most widely used questionnaires to assess career adaptability. To facilitate its integration into large surveys, in varied settings, the aim of this article was to develop a brief 12-item version, the Career Adapt-Abilities Scale-Short Form (CAAS-SF). A sample of 2,800 French-and German-speaking adults living in Switzerland completed the CAAS. On a first random subsample, a principal component analyses conducted on the CAAS-SF suggested a four-facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
209
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(248 citation statements)
references
References 28 publications
22
209
0
7
Order By: Relevance
“…Participants responded on 5-point Likert-type scales (1 = not a strength and 5 = greatest strength). Maggiori et al (2017) confirmed the hierarchical factor structure of career adaptability, which warrants the computation of an overall career adaptability score across subdimensions.…”
Section: Career Adaptability (Caas-sf)supporting
confidence: 62%
See 1 more Smart Citation
“…Participants responded on 5-point Likert-type scales (1 = not a strength and 5 = greatest strength). Maggiori et al (2017) confirmed the hierarchical factor structure of career adaptability, which warrants the computation of an overall career adaptability score across subdimensions.…”
Section: Career Adaptability (Caas-sf)supporting
confidence: 62%
“…Career adaptability was assessed with the German Career Adapt-Abilities Scale -Short Form (CAAS-SF; Maggiori, Rossier, & Savickas, 2017), which is a brief 12-item version of the widely used Career Adapt-Abilities Scale (CAAS) by Savickas and Porfeli (2012). The CAAS-SF assesses each of the four theoretical subdimensions of career adaptability with three items, including concern (e.g., 'Preparing for the future'), control (e.g., 'Taking responsibility for my actions'), curiosity (e.g., 'Looking for opportunities to grow as a person'), and confidence (e.g., 'Taking care to do things well').…”
Section: Career Adaptability (Caas-sf)mentioning
confidence: 99%
“…Career adaptability. Career adaptability was measured using the Career Adapt-Abilities Scale-Short Form (CAAS-SF; Maggiori, Rossier, & Savickas, 2017). The scale consists of 12 items and measures four career adaptability facets: concern (e.g., "Thinking about what my future will be like"), control (e.g., "Taking responsibility for my actions"), curiosity (e.g., "Looking for opportunities to grow as a person"), and confidence (e.g., "Taking care to do things well").…”
Section: Methodsmentioning
confidence: 99%
“…by Maggiori, Rossier, and Savickas (2015). The scale contains four subscales with 3 items each to measure the adaptive resources of concern, control, curiosity and confidence respectively.…”
Section: Career Adaptability Career Adaptability Was Measured By Thementioning
confidence: 99%